2013
DOI: 10.4236/ojop.2013.24013
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Objective Optimization of Low Impact Development Designs in an Urbanizing Watershed

Abstract: Multi-objective optimization linked with an urban stormwater model is used in this study to identify cost-effective low impact development (LID) implementation designs for small urbanizing watersheds. The epsilon-Non-Dominated Sorting Genetic Algorithm II (ε-NSGAII) has been coupled with the US Environmental Protection Agency's Stormwater Management Model (SWMM) to balance the costs and the hydrologic benefits of candidate LID solutions. Our objective in this study is to identify the near-optimal tradeoff betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…The study of [54] couples SWMM5 with NSGA-II to size and distribute drainage solutions, using decentralized and centralized measures for flood reduction, considering cost minimization and enhancement of ecosystem services. In another work, Zhang et al [55] applied multi-objective optimization to identify cost-effective practices in a watershed to be developed. Finally, Ahiablame et al [56] presented a review of effectiveness of sustainable measures and among the gaps identified they call for the necessity of watershed and regional scale evaluations, and the development of practical decision making tools.…”
Section: The Use Of Hydrodynamic and Optimization Models For Evaluatimentioning
confidence: 99%
“…The study of [54] couples SWMM5 with NSGA-II to size and distribute drainage solutions, using decentralized and centralized measures for flood reduction, considering cost minimization and enhancement of ecosystem services. In another work, Zhang et al [55] applied multi-objective optimization to identify cost-effective practices in a watershed to be developed. Finally, Ahiablame et al [56] presented a review of effectiveness of sustainable measures and among the gaps identified they call for the necessity of watershed and regional scale evaluations, and the development of practical decision making tools.…”
Section: The Use Of Hydrodynamic and Optimization Models For Evaluatimentioning
confidence: 99%
“…The most advanced tool is EPA's Storm Water Management Model (SWMM) [27]. It is a dynamic rainfall-runoff and hydraulic simulation engine that was designed to predict the resultant runoff in urban areas from each modeled subcatchment in response to precipitation input [28,29,30,31]. Research conducted on estimating surface runoff volumes in major cities of Turkey has commonly concluded that tight resource management aiming to use alternative water resources such as rainwater are required for better environment, health and economy [32,33,34,35,36,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…PerezPedini et al (2005) described a distributed hydrologic model combined with a genetic algorithm to determine the optimal location of infiltration-based BMP. Zhang (2006) used a revised version of the non-dominated sorted genetic algorithm-II (NSGA-II) and epsilon non-dominated sorted genetic algorithm to optimize various low impact development designs in an urbanizing watershed. Oraei Zare et al (2012) studied technologies that coupled the storm water management model (SWMM) with NSGA-II to control both the quality and quantity of urban floods.…”
Section: Introductionmentioning
confidence: 99%